Discovery and biological evaluation of 1-2, 7-diazaspiro[3.5]nonan-2-ylprop-2-en-1-one derivatives as covalent inhibitors of KRAS G12C with favorable metabolic stability and anti-tumor activity. (1st October 2022) - Imaizumi, Tomoyoshi; Akaiwa, Michinori; Abe, Tomoaki; Nigawara, Takahiro; Koike, Takanori; Satake, Yoshiki; Watanabe, Kazushi; Kaneko, Osamu; Amano, Yasushi; Mori, Kenichi; Yamanaka, Yosuke; Nagashima, Takeyuki; et al.
Graphical abstract: Abstract: RAS protein plays a key role in cellular proliferation and differentiation. RAS gene mutation is a known driver of oncogenic alternation in human cancer. RAS inhibition is an effective therapeutic treatment for solid tumors, but RAS protein has been classified as an undruggable target. Recent reports have demonstrated that a covalent binder to KRAS protein at a mutated cysteine residue (G12C) is effective for the treatment of solid tumors. Here, we report a series of 1-2, 7-diazaspiro[3.5]nonan-2-ylprop-2-en-1-one derivatives as potent covalent inhibitors against KRAS G12C identified throughout structural optimization of an acryloyl amine moiety to improve in vitro inhibitory activity. From an X-ray complex structural analysis, the 1- 2, 7-diazaspiro[3.5]nonan-2-ylprop-2-en-1-one moiety binds in the switch-II pocket of KRAS G12C. Further optimization of the lead compound (5c ) led to the successful identification of 1-[7-[6-chloro-8-fluoro-7-(5-methyl-1H-indazol-4-yl)-2-[(1-methylpiperidin-4-yl)amino]quinazolin-4-yl]-2, 7-diazaspiro[3.5]nonan-2-yl]prop-2-en-1-one (7b ), a potent compound with high metabolic stabilities in human and mouse liver microsomes. Compound 7b showed a dose-dependent antitumor effect on subcutaneous administration in an NCI-H1373 xenograft mouse model.